New Insights into the Role of Surface Nanobubbles in Bubble-Particle Detachment - Ding, Shihao (Langmuir : the ACS journal of surfaces and colloids, 2020)
It is well recognized that an improved flotation recovery can be achieved by introducing nanobubbles to common flotation practice due to the increased capture efficiency between bubbles and particles. However, the specific role of nanobubbles in bubble-particle interactions (collision, attachment, and detachment) is not well understood. In the present study, we explore the role of surface nanobubbles in bubble-particle detachment. Surface nanobubbles were introduced via ethanol-water exchange and their presence was confirmed using laser scanning confocal microscopy (LSCM). The effect of surface nanobubbles on bubble-particle detachment behavior was then investigated using an oscillating bubble apparatus. Bubble-particle aggregate stability was evaluated using critical detachment amplitude. Further, bubble-particle detachment forces in the absence and presence of nanobubbles were measured directly using a micro-nano mechanical testing system. Using LSCM, numerous surface nanobubbles were observed on a glass surface after ethanol-water exchange, regardless of wettability. The number and lateral dimensions of generated nanobubbles on the hydrophilic surface were significantly smaller than that on the hydrophobic surface. Surface nanobubbles increased the stability of bubble-particle aggregates. Macroscopic air bubbles coalesce with the nanobubbles on the particle surface, increasing the pinning effect of the three-phase contact line and advancing contact angle. As a result, the capillary force between bubbles and particles increased in the presence of surface nanobubbles